(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2022)
Back pain and menstruation pain are generally treated with a combination of paracetamol (PCM) and pamabrom (PAMA). In this study, a liquid chromatography/tandem mass spectrometry (LC-MS/MS) method for the simultaneous quantification of PCM and PAMA from human plasma is developed and validated for the first time. The analytes and the internal standard (IS), diclofenac, were eluted on a kromasil C18 (100 x 4.6 mm, 5 μm) column using a simple optimized mobile phase after being treated by liquid-liquid extraction. Using the electrospray ionization technique, quantification was carried out using a hyphenated tandem mass spectrometer with a flow rate of 0.4 mL/min and completing the entire run time within 4 minutes. For PCM and PAMA, the calibration curve was linear (r > 0.995) for the range of 40–8000 ng/mL and 20–4000 ng/mL, respectively. This method produced reliable findings since it was verified for specificity, accuracy, recovery, linearity, precision, matrix effect, and stability investigations, and the results were determined to be within acceptable parameters. The current study’s findings demonstrated that this technology’s simplicity, rapidity, and sensitivity allow for routine usage in exploratory or clinical monitoring of both medications in human plasma.